Thai University Students’ Perceptions of Factors Affecting the Thai Tourism Industry: A Case Study - Janpha Thadphoothon (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: The aim of this study was to investigate Thai university students’ perceptions of the factors that would affect the tourism industry of Thailand. Method:  Forty-five (45) undergraduates in a university in Thailand were asked to answer the questionnaire of nine questions on the effects of selected factors affecting the Thai tourism industry. The data collection was done in March 2021. The collected data were analyzed using basic descriptive statistics. Result: The results showed that Covid-19 pandemic was perceived to be the factor with the greatest impact on Thai tourism (Mean = 4.86), followed closely by the internal political problems (Mean = 4.40). .The lowest three factors were found to be the climate crises (Mean = 3.64), US-China trade war (Mean = 3.55), and robots/AI (Mean = 3.13). Foreign language skills, communication, and technology use were among the highly cited skills and abilities Thai people should be focusing more on. Contribution: This study adds valuable insights to the existing body of knowledge in the field of tourism and hospitality management. The findings provide a perspective on the factors influencing the industry's performance, especially  revealing the intricate interplay between socio-political, environmental, and economic factors.